The frequency of small saccades during fixation is age independent in children between 5 and 16 years of age. Issue 1 (18th August 2016) - Larsen, Dorte Ancher; Bek, Toke
Abstract: Purpose: Fixational eye movements are necessary for maintaining normal vision by preventing a stabilized image on the retina that would result in visual fading. The movements can be divided into tremor, drifts and saccades that may be related to movements of gaze and to fixation. It has previously been shown that the frequency of fixational saccades with an amplitude larger than 3° depends on age. The purpose of this study was to investigate whether other parameters describing fixational saccades also depend on age which necessitates age correction in studies of fixation during visual development. Methods: Fixational eye movements were recorded in 36 normal children aged 5–16 years. Parameters describing fixational saccades were characterized using a standardized algorithm and were correlated with age. Results: There was a significant linear relation between the amplitude and duration of fixational saccades ( r 2  = 0.37, p < 0.0001). The relation between the number of saccadic movements and the amplitude was unimodal and showed no correlation with age. However, the number of saccades per examination with an amplitude larger than 1° showed a negative correlation with age ( r 2  = 0.23, p = 0.003). Conclusions: The overall frequency and amplitude of fixational saccades show no correlation with age that necessitates correction in clinical studies of visual development. The decreasing frequency of large saccadic eye movements with increasing child age may be due to improved attention.